Implementasi Metode Waterfall Pada Pengembangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada SMK Negeri 2 Adiwerna - Fandhilah Fandhilah; Atika Okta Rindina; Devy Ferdiansyah; Ahmad Ishaq (Indonesian Journal on Software Engineering (IJSE), 2019)
Abstract: The development of information technology more advanced and very rapidly, one of which is the internet. Wtih the internet, people are easier in getting information quickly and efficiently. Especially in the provision of information for an organization/institution or company that requires data management system quicly, precisely and accurately. With the internet , an institution such as school can provide more complete information, up to date, interavtive adn dynamic. At SMK Negeri 2 Adiwerna information system related to school still dilevered in the form of manual book and acceptnce of new student still done manually. Recap process also has not run optimally so often the occuranceof data errors. In addition, applicants not only come from Tegal even outside Tegal aea that requires parents and prospective students to come to school to obtain information about the school and make the regristation process causing long quees, resulting in less efficiency in time and a lot of costs tobe incurred. That’s why the author tries to make the new web base admissins information system at SMK Negeri 2 Adiwerna. Trough this system is expected to facilitate prospective students and parents in getting information about the school without having to come queuing to school. Keyword: Information System, New Student Reception SMK Negeri 2 Adiwerna Online